2015
DOI: 10.1371/journal.pone.0126991
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Anthocyanin Biosynthesis-Modulating Potential of Sweet Cherry (Prunus avium L.) MYB10 and bHLH Genes

Abstract: Anthocyanins are essential contributors to fruit coloration, an important quality feature and a breed determining trait of a sweet cherry fruit. It is well established that the biosynthesis of anthocyanins is regulated by an interplay of specific transcription factors belonging to MYB and bHLH families accompanied by a WD40 protein. In this study, we isolated and analyzed PaWD40, PabHLH3, PabHLH33, and several closely related MYB10 gene variants from different cultivars of sweet cherry, analyzed their expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 34 publications
(54 reference statements)
6
53
0
Order By: Relevance
“…It is speculated that this occurrence is associated with the coordination of plant metabolism because of the ability of plants to regulate the metabolism in respective organs at various developmental stages (Majdi et al, 2014). These results concur with those found in yam, cherry, grape, and chili (Aza-Gonzalez et al, 2013; Liu et al, 2013; Xie et al, 2015; Yin et al, 2015). There was also a difference in the accumulation of anthocyanin in tissues of different radish at each developmental stage.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is speculated that this occurrence is associated with the coordination of plant metabolism because of the ability of plants to regulate the metabolism in respective organs at various developmental stages (Majdi et al, 2014). These results concur with those found in yam, cherry, grape, and chili (Aza-Gonzalez et al, 2013; Liu et al, 2013; Xie et al, 2015; Yin et al, 2015). There was also a difference in the accumulation of anthocyanin in tissues of different radish at each developmental stage.…”
Section: Discussionsupporting
confidence: 90%
“…These include cherry (Liu et al, 2013), dendrobium (Kriangphan et al, 2015), mulberry (Li et al, 2014), grape (Xie et al, 2015) and yam (Yin et al, 2015). It was suggested that patterns of anthocyanin biosynthesis in different grape berry tissues are discontinuous, implying that ABGs are regulated spatially and temporally (Falginella et al, 2012; Xie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Starkevič isolated and analysed several closely related MYB10 genes from different cultivars of sweet cherry. Their results indicated that transcription level of variant PaMYB10.1 correlates with fruit coloration (Starkevič et al ., ). In this study, PavMYB10.1 and PavMYB10.2 were mapped to the same region on LG 3 (Figure ).…”
Section: Discussionmentioning
confidence: 97%
“…Several MYB10 genes were isolated and analysed from different cultivars of sweet cherry. By homology to the related peach genes, the shorter gene was named PaMYB10.1 , and the longer was named PaMYB10.2 (Starkevič et al ., ). The role of the homologues and orthologues of these genes as regulators of anthocyanin biosynthesis has been shown previously in Prunus species.…”
Section: Introductionmentioning
confidence: 97%
“…In certain plants, MYB proteins regulate anthocyanin biosynthesis by interacting with bHLH proteins, a mechanism that has been widely studied in petunias (Quattrocchio et al, 2006;Boase et al, 2015), snapdragons (Schwinn et al, 2006;Butelli et al, 2008), and maize (Grotewold et al, 1998;Dong et al, 2015). In Arabidopsis thaliana, TT2, TT8, and TTG1 encode an R2R3-MYB domain protein, a bHLH transcription factor, and a WD40-repeat-containing protein, respectively, and their tripartite interaction regulates expression of flavonoid structural genes (Nesi et al, 2001;Starkevič et al, 2015). In this study, expression of the MYB10 gene was high, and correlated with elevated anthocyanin content in red-leaf peach (Figures 11 and 12).…”
Section: Discussionmentioning
confidence: 56%